Trading restrictions and firm dividends: The share lockup expiration experience in China - Fang, Hongyan; Song, Zhihui; Nofsinger, John R.; Wang, Yuyue (Journal of Banking & Finance, 2017)
Chinese firms experienced a substantial reduction in nontradable shares following the Split-Share Structure Reform that began in 2005. The decrease in nontradable shares, or increase in share tradability, is associated with a decline in the firms’ cash dividend payouts. The positive association is attenuated in firms with fewer financial constraints, only weakly affected by firm governance, and not affected by investment opportunities or controlling shareholder type. The results highlight the fact that firms disgorge cash to compensate shareholders for trading restrictions and conclude that dividends persist when firms have easier access to external financing. These findings are robust to alternative definitions of nontradable shares, after controlling for firm fixed effects and omitted changing firm characteristics.